Improving Students’ Speaking Skills Through Alice in Wonderland Movie for Eleventh-Grade Students of MAS Maftahul Falah Sekacer Academic Year 2023/3024 - Widoretno, Olga Junior; Putri, Aprilia Riyana (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
The purpose of this study is to decide whether or not watching films helps students improve their speaking abilities. This research focused on how English movies' effects are applied to learning. Researchers used pre-experimental research, which included just one class in the study. MAS Maftahul Falah, who was in eleventh grade, was the population of this research. The researcher selected the sample using saturation sampling. The 18 students are the subject of the research in the academic year 2023/2024 to participate in a project to observe how their speaking ability develops. Testing of the instruments was conducted during the data collection process, before and after the treatment. The result showed that the mean score of the post-test was higher than score of the pre-test (72.50 > 61.33). This indicated that there was a significant effect on post-test results. Then, the result of the hypothesis analysis showed that the 2-tailed sig value was lower than alpha (0.000 < 0.05). This means that H0 is rejected and Ha is accepted. From these results, there were significant effects of the use of Alice in Wonderland movie as teaching media on students’ speaking skills.